DETERMINAN MINAT PEMBELIAN KEBAYA WISUDA: PERAN PERSEPSI KUALITAS, PERSEPSI HARGA DAN INOVASI PRODUK PADA MAHASISWA GENERASI Z - Rika Selvia; hartini (Publika Citra Media, 2026)
This study aims to analyze the influence of quality perception, price perception, and product innovation on the purchase intention of graduation kebaya among students at Universitas Teknologi Sumbawa. Employing a quantitative approach with survey method, the study involved 100 female students in their 7th semester completing their final thesis. Data were collected through questionnaires and analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. Results indicate that quality perception (β=0.313; p<0.05), price perception (β=0.404; p<0.05), and product innovation (β=0.370; p<0.05) have positive and significant effects on purchase intention. Price perception has the strongest influence, followed by product innovation and quality perception. These three variables explain 41.8% of the variance in purchase intention (R²=0.418). The study recommends business owners optimize competitive pricing strategies, enhance product quality, and develop innovations aligned with Generation Z students' preferences to increase competitiveness.